J. MONCLÚS, C. DÍEZ MEDINA (eds.) - Ciudad y formas urbanas. Perspectivas transversales, Actas del II Congreso Internacional ISUF-H (Hispanic International Seminar on Urban Form) - Sucena, Sara (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Javier Monclús and Carmen Díez Medina (eds.) Ciudad y formas urbanas. Perspectivas transversales, Actas del II Congreso Internacional ISUF-H (Hispanic International Seminar on Urban Form) Zaragoza: PUZ, 2018 (10 vol). Language: Spanish. Hardcover. 20 € /volume. ISBN 978-84-17358-90-7